Understanding the School Curriculum: Theory, Politics and Principles - Goh, Daeyoung (Journal of the Canadian Association for Curriculum Studies, 2021)
Alex Moore’s (2015) Understanding the School Curriculum: Theory, Politics and Principles explores how the school curriculum works through its becoming as it navigates reproductive paranoia and (r)evolutionary schizophrenia. Moore suggests that the school curriculum inevitably intersects with political and socio-economic interests as well as the globalization movement. In this light, the book stimulates the reader to ponder questions such as, “Who decides what kind of knowledge we should have in this wider, ever-changing world?” and “How have issues around knowledge developed with the school curriculum?” and “What sort of future could educators imagine for alternative knowledge, educational practice and society?” Such questions haunt the book, while promoting the educator and the learner to risk weaving a creative becoming and thereby moving the realm of knowledge from the boundary of instrumental rationality to the horizon of dynamics of humanity.